Влияние 2,4-Д и БАП на эмбриогенную способность у сомаклонов винограда - Марченко, А.О. (Физиология и биохимия культурных растений, 2009)
Изучено влияние содержания 2,4-Д и БАП в среде культивирования на эмбриогенную способность у сомаклонов винограда и на сомаклональную изменчивость. У сомаклонов, полученных при использовании 1 мг/л 2,4-Д, фенотипические изменения отсутствовали, при использовании 3 мг/л 2,4-Д - изменялась гормональная зависимость эмбриоидогенеза; они различались и по морфологическим, и по фенологическим признакам. Сделаны выводы, что с помощью 2,4-Д и цитокининов можно управлять сомаклональной изменчивостью; последняя связана с изменением регуляторной системы у сомаклонов, которые рассматриваются как модельная система для изучения закономерностей реорганизации генома. Вивчали вплив вмісту 2,4-Д і БАП у середовищі культивування на ембріогенну здатність у сомаклонів винограду і на сомаклональну мінливість. У сомаклонів, отриманих за використання 1 мг/л 2,4-Д, фенотипних змін не було, за використання 3 мг/л 2,4-Д — змінювалась гормональна залежність ембріоїдогенезу; вони різнилися як за морфологічними. так і за фенологічними ознаками. Зроблено висновки, що за допомогою 2,4-Д і цитокінінів можна керувати сомаклональною мінливістю; остання пов'язана зі зміною регуляторної системи у сомаклонів, які розглядаються як модельна система для вивчення закономірностей реорганізації геному. The effects of 2,4-D and BAP on embryogenic capacity at grape somaclones (passing more than 40 cycles of vegetative reproduction and two cycles of embryoidogenesis) and on somaclonal variation were studied. Grape plants obtained through somatic embryogenesis using 3 mg/l 2,4-D showed a different embryogenic capacity with refer to the cytokinin levels applied. Analysis of somaclones in general showed that plants obtained by inducing embryogenic callus at 1 mg/l of 2,4-D had no phenotypic alterations. At the same time, plants obtained with 3 mg/l of 2,4-D included forms that differed in morphological and phenological traits. It was concluded that: it is possible to manage somaclonal variation by 2,4-D and cytokinins; somaclonal variation is related to the change of the regulator system at somaclones, which are concerned as a model system for the study of reorganization of genome.